Magnetic resonance imaging in cervical cancer interventional radiotherapy (brachytherapy): a pictorial essay focused on radiologist management - Russo, Luca; Lancellotta, Valentina; Miccò, Maura; Fionda, Bruno; Avesani, Giacomo; Rovirosa, Angeles; Wojcieszek, Piotr; Scambia, Giovanni; Manfredi, Riccardo; Tagliaferri, Luca; Gui, Benedetta (Journal of Contemporary Brachytherapy, 2022)
The standard treatment for locally advanced cervical cancer (LACC) is platinum-based chemotherapy in association with external beam radiotherapy (EBRT) and brachytherapy (BT), often also called ‘interventional radiotherapy’ (IRT). Magnetic resonance imaging (MRI) is the most accurate imaging modality for both staging and response evaluation; therefore MRI-guided IRT has become the method of choice for planning a radiation boost after EBRT. The aim of this paper was to describe the MRI radiological workflow currently ongoing at our Institution. In addition, we provided a detailed pictorial essay of our experience, especially for radiologists, to implement MRI-based IRT spread in clinical practice.